PENGARUH SUASANA CAFE, LOKASI DAN KUALITAS PELAYANAN TERHADAP MINAT BELI ULANG DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA CAFE KEDAI SIRING JANGKAR SITUBONDO - Nida Nuriyana; Randika Fandiyanto; Ida Subaida (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
At Café Kedai Siring, location was found to affect purchasing decisions. The cafés position near a quiet beach but far from residential areas increases parking security risks, while service quality was considered lacking due to long service times, order errors, and limited facilities. This study analyzes the effects of café atmosphere, location, and service quality on repurchase intention, with customer satisfaction as an intervening variable. The research used a quantitative approach with 99 respondents selected through simple random sampling, and data were analyzed using the PLS-SEM method with SmartPLS 3.0. The results showed that café atmosphere, location, and service quality significantly influenced customer satisfaction. Café atmosphere and location had a significant positive effect on repurchase intention, while service quality had a positive but not significant effect. Customer satisfaction itself had a significant effect on repurchase intention and mediated the influence of café atmosphere, location, and service quality on repurchase intention.